Avaliação da erupção de dentes decíduos entre crianças nascidas com baixo peso e com peso normal - Silveira, Roberto da Gama (2000)
Verify by means of examining the chronology and frequency of the eruption of the primary teeth found in children born with normal birth weight (>2.500 gr.) and with low birth weight (> or = 2.500 gr.) taking into consideration their mothers' ages; marital status, as well as the kind of birth they had. The study was done at UNIGRANRIO'S babies clinics, Duque de Caxias, RJ - Brazil. 333 children they were selected the both sexes (49.5% male and 50.5% female), 312 from the group of children born with normal weight and 19 born with low birth weight. The incidence of low birth weight found as a result of studying the samples was 5.7% in relation to children born with normal weight. The average age of the children's mothers born with normal weight was 27% whereas in the group of low birth weight was 26.3%. 70.6% of the children born with low birth weight were had a normal birth, whereas in the group of the normal weight it was 63%. Furthermore, there was no meaningful difference found with regard to the actual age of the primary teeth, in spite of the precocity of the eruption in all male children. About the weight at birth, it was not observed significant difference statistically, in relation to the average of the eruption of primary teeth, in spite of verifying that the eruption of primary teeth in children from the group of low birth weight was late, in comparison to the children with normal weight.